2021
DOI: 10.1111/ane.13434
|View full text |Cite
|
Sign up to set email alerts
|

Swedish guidelines for device‐aided therapies in Parkinson's disease —Economic evaluation and implementation

Abstract: Objectives The National Board of Health and Welfare in Sweden published the national guidelines for Parkinson's Disease 2016. The aim of this study was to summarize this evidence review and development of the guidelines, focusing on the economic evaluation of device‐aided therapies (deep brain stimulation, pump‐based infusion of levodopa‐carbidopa intestinal gel or apomorphine) for Parkinson's disease, and the rate of implementation after 3 years in Sweden. Material and methods The evidence review underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…An analysis of prescription of DATs in Sweden published in 2021 found that while their use has increased in Sweden since evidence-based treatment guidelines were published in 2016, it is still not at the levels suggested in these recommendations. 22 …”
Section: Options For the Delivery Of Continuous Dopaminergic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of prescription of DATs in Sweden published in 2021 found that while their use has increased in Sweden since evidence-based treatment guidelines were published in 2016, it is still not at the levels suggested in these recommendations. 22 …”
Section: Options For the Delivery Of Continuous Dopaminergic Stimulationmentioning
confidence: 99%
“…Sweden has a National Parkinson’s Disease Patient Registry (PARKreg) as part of the Swedish Neuro Registry ( https://www.neuroreg.se ). 22 So far, more than 100 patients on LECIG are registered in Sweden. Alongside the launch of LECIG infusion, a prospective, noninterventional, observational pan-European study has been established.…”
Section: Real-world Clinical Experience With Lecig Infusionmentioning
confidence: 99%
“…20 In view of the cost-effectiveness of DAT therapies, 10 this is an encouraging development, especially taking into account the recommended use of DAT. 14 The barriers to and the possible reasons for underutilization of DAT in Poland remain unclear, but it can be speculated that several factors may be involved: 1) the relatively high initial costs of DAT 6 ; 2) the limited availability of DATs; 3) the relatively low number of specialized movement disorder neurologists 10 ; 4) a conservative approach to PD treatment in general 15 ; 5) the low number of referrals by general neurologists and general practitioners due to limited knowledge about DAT 21,22 ; and 6) limited knowledge about DAT among persons with PD. 23 While using a national registry helps minimize selection bias, there are still some limitations to consider.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of early fluctuations and dyskinesia is delayed in many cases due to multiple circumstances, such as the short neurology visits and the lack of optimal tools, which can allow for precise symptom identification. This circumstance is also present in advanced stages, where there is also an infradiagnosis of advanced symptoms ( 9 , 10 ). So far, the identification and quantification of MF can be measured through patient diaries (e.g., Hauser diaries) and/or by a set of validated scales, such as the Unified Parkinson's Disease Rating Scale (UPDRS) ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%